Antifogging material, hardened body, laminate, optical article, lens, and glasses

JP2025034019APending Publication Date: 2025-03-13TOKUYAMA CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023140137
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0011】 本発明によると、防曇性に優れ、かつ、高い硬度を有する硬化体を実現可能な防曇材料と、この硬化体、積層体、光学物品、レンズ、及び眼鏡とが提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034019000001_ABST
    Figure 2025034019000001_ABST
Patent Text Reader

Abstract

To provide: an antifogging material capable of achieving a hardened body having excellent antifogging properties and high hardness; and the hardened body, a laminate, an optical article, a lens, and glasses, each using the antifogging material.SOLUTION: According to an embodiment, an antifogging material is provided. The antifogging material includes alkoxysilane having an urea bond. According to another embodiment, a hardened body is provided. The hardened body is a hardened body of the antifogging material according to the embodiment. A laminate is provided according to another embodiment. The laminate includes an optical substrate and an antifogging coating layer. The antifogging coating layer includes the hardened body according to the embodiment.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an anti-fog material, a cured product, a laminate, an optical article, a lens, and glasses. [Background technology]

[0002] Plastic or glass lenses are known as eyeglass lenses. The surfaces of these lenses may be coated with an anti-fog coating. For example, siloxane, an organic-inorganic composite material, is used as the material for the anti-fog coating. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2018-528289 [Patent Document 2] Patent Publication No. 2022-71754 [Patent Document 3] JP 2022-152981 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide an anti-fogging material capable of producing a cured product having excellent anti-fogging properties and high hardness, and to provide said cured product, a laminate, an optical article, a lens, and a pair of glasses. [Means for solving the problem]

[0005] The present disclosure relates to an anti-fogging material. The anti-fogging material includes an alkoxysilane having a urea bond.

[0006] The present disclosure relates to a cured body, which is a cured body of an anti-fog material according to the present disclosure.

[0007] The present disclosure relates to a laminate. The laminate includes an optical substrate and an anti-fog coating layer. The anti-fog coating layer includes a cured product according to the present disclosure.

[0008] The present disclosure relates to an optical article. The optical article includes a cured body according to the present disclosure.

[0009] The present disclosure relates to a lens, the lens comprising an optical article according to the present disclosure.

[0010] The present disclosure relates to eyeglasses comprising lenses according to the present disclosure. Effect of the Invention

[0011] According to the present invention, there are provided an anti-fogging material capable of realizing a cured product having excellent anti-fogging properties and high hardness, and the cured product, a laminate, an optical article, a lens, and a pair of glasses. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a cross-sectional view illustrating an example of a laminate according to an embodiment. [Diagram 2] FIG. 1 is a perspective view illustrating an example of glasses according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] According to an embodiment, an anti-fogging material is provided. The anti-fogging material includes an alkoxysilane having a urea bond. Since the alkoxysilane has a urea bond, it is possible to realize a cured body having excellent anti-fogging properties and high hardness. It is also believed that the adhesion to a plastic substrate is improved.

[0014] The anti-fogging material according to the embodiment will be described in detail below.

[0015] [Anti-fogging material] The anti-fogging material according to the embodiment includes an alkoxysilane having a urea bond. The anti-fogging material according to the embodiment may be composed of only an alkoxysilane having a urea bond, or may include a component other than the alkoxysilane having a urea bond. That is, the anti-fogging material according to the embodiment may be a curable composition for forming an anti-fogging coat.

[0016] The alkoxysilane preferably has a trialkoxysilane group represented by the following formula (I).

[0017] [ka]

[0018] In formula (I), R 1 and R 2 R is each independently a linear or branched alkylene group having 1 to 10 carbon atoms. 1 and R 2 are each independently preferably a linear alkylene group having 1 to 5 carbon atoms, and more preferably a methylene group, an ethylene group, or a propylene group.

[0019] R 3 R is a linear alkyl group having 1 to 5 carbon atoms. 3 is preferably an alkyl group having 1 to 3 carbon atoms, and more preferably a methyl group or an ethyl group. a is 0 or 1.

[0020] Examples of compounds having a trialkoxysilane group represented by formula (I) include 3-ureidopropyltriethoxysilane represented by formula (Ia) below and N,N'-bis(triethoxysilylpropyl)urea represented by formula (Ib):

[0021] [ka]

[0022] [ka]

[0023] The alkoxysilane preferably includes a trialkoxysilane represented by the following formula (II):

[0024] [ka]

[0025] In formula (II), R 1 , R 2 , and R 3 has the same meaning as in formula (I). R 4 and R 5 R is each independently a linear or branched alkylene group having 1 to 10 carbon atoms. 4 and R 5 are each independently preferably a linear alkylene group having 1 to 5 carbon atoms, and more preferably a methylene group, an ethylene group, or a propylene group.

[0026] R 6 is -Si(OR 3 )3, or a hydroxy group. 6 is -Si(OR 3 )3 is preferred. b is 0 or 1.

[0027] Examples of the trialkoxysilane represented by formula (II) include N-(2-hydroxyethyl)-N'-[3-(triethoxysilyl)propyl]urea (HETESPU) represented by the following formula (IIa) and N-[3-(triethoxysilyl)propyl]-N'-(3-triethoxysilylpropylaminoethyl)urea (BTESAU) represented by the following formula (IIb).

[0028] [ka]

[0029] [ka]

[0030] The trialkoxysilane represented by formula (II) can be synthesized by a known method. The alkoxysilane may include a trialkoxysilane represented by the following formula (III).

[0031] [ka]

[0032] In formula (III), X is a trialkoxysilane group represented by formula (I). A plurality of X's may be the same group or different groups.

[0033] Y is nitrogen, a linear or branched alkylene group having from 1 to 10 carbon atoms, a cycloalkylene group having from 4 to 10 carbon atoms, or an arylene group having from 4 to 8 carbon atoms. Y is preferably nitrogen or a phenylene group.

[0034] R 7 R is a linear or branched alkylene group having 1 to 10 carbon atoms. 7 If there are multiple R 7 may be the same group or different groups. c is 0 or 1.

[0035] d is 3 when Y is nitrogen and 2 when Y is a group other than nitrogen. Examples of the trialkoxysilane represented by formula (III) include tris[(triethoxysilylpropylaminocarbonylamino)ethyl]amine (TTESAU) represented by the following formula (IIIa) and N,N'-bis[(triethoxysilyl)propyl]aminocarbonyl-m-xylylenediamine (BTESUmX) represented by the following formula (IIIb).

[0036] [ka]

[0037] [ka]

[0038] The trialkoxysilane represented by formula (III) can be synthesized by a known method.

[0039] In the anti-fogging material, the content of the alkoxysilane having a urea bond is, for example, 10% by mass or more and 99% by mass or less, preferably 15% by mass or more and 90% by mass or less, and more preferably 20% by mass or more and 80% by mass or less.

[0040] The anti-fogging material may further contain silica sol. When silica sol is contained, it is expected that the hardness is improved. The average particle size of the silica particles in the silica sol is, for example, 10 nm or more and 200 nm or less by dynamic light scattering method. The ratio of the organic solvent in the silica sol is, for example, 10 mass % or more and 50 mass % or less. For example, methanol, methyl ethyl ketone, etc. can be used as the organic solvent.

[0041] The proportion of silica sol in the anti-fogging material is, for example, 0.1% by mass or more and 10% by mass or less, and preferably 1% by mass or more and 5% by mass or less.

[0042] The anti-fogging material may also include other alkoxysilanes. The other alkoxysilanes typically do not have a urea bond. The other alkoxysilanes preferably include a functional group such as an epoxy group, a glycidyl group, an amino group, or a hydroxyl group, and more preferably include an epoxy group or a glycidyl group.

[0043] Examples of the silane coupling agent that can be used include bis[3-(trimethoxysilyl)propyl]amine (BTESPA), 3-aminopropyltriethoxysilane (APTES), 3-glycidyloxypropyltrimethoxysilane (TEGPS), and hydroxymethyltriethoxysilane.

[0044] In the anti-fogging material, the proportion of the other alkoxysilanes is, for example, from 0 mass % to 50 mass %, and preferably from 0 mass % to 20 mass %.

[0045] The anti-fogging material may further contain a solvent. As the solvent, an organic solvent having 1 to 5 carbon atoms, water, or a mixture of these may be used. As the organic solvent having 1 to 5 carbon atoms, it is preferable to use methanol, ethanol, 1-propanol, 2-propanol, THF, acetone, ethyl methyl ketone, or a mixture of these.

[0046] In the anti-fogging material, the proportion of the solvent is, for example, from 0 mass % to 10 mass %, and preferably from 0 mass % to 5 mass %.

[0047] The antifogging material may further include silica particles. When the silica particles are included, the hardness can be improved. The average particle size of the silica particles measured by dynamic light scattering is, for example, 10 nm or more and 200 nm or less. The antifogging material may be a composite polymer of the above-mentioned alkoxysilane having a urea bond and silica particles. In this composite polymer, the ratio M2 / M1 of the mass M1 of the alkoxysilane having a urea bond to the mass M2 of the silica particles is, for example, 0.001 or more and 0.10 or less, and preferably 0.005 or more and 0.05 or less.

[0048] This composite polymer may be dissolved in the above-mentioned solvent to form a curable composition which can be used as an anti-fogging material.

[0049] [Laminate] The laminate according to the embodiment includes an optical substrate and an anti-fog coating layer including a cured product of the anti-fog material according to the embodiment. The anti-fog coating layer is located on the surface of the optical substrate. Other functional layers may be included between the anti-fog coating layer and the optical substrate. Examples of the other functional layers include a photochromic layer, an adhesive layer, a hard coat layer, an anti-reflective film, an antifouling coat, and a water-repellent coat. The laminate according to the embodiment may be a laminate in which the optical substrate, the adhesive layer, the hard coat layer, the anti-reflective film, and the anti-fog coating layer are laminated in this order.

[0050] Fig. 1 is a cross-sectional view that illustrates an example of a laminate according to an embodiment. The laminate 10 illustrated in Fig. 1 includes an optical substrate 11 and an anti-fog coating layer 1. The laminate 10 has a concave-convex lens shape. The laminate 1 has a curved surface that conforms to the shape of the lens.

[0051] The optical substrate may comprise a resin or an inorganic material such as glass, etc. The optical substrate may be a glass lens substrate or a plastic lens substrate.

[0052] The thickness of the optical substrate is, for example, 0.1 mm or more and 20 mm or less, and preferably 0.5 m or more and 10 m or less.

[0053] The resin for the optical substrate may be at least one resin selected from the group consisting of allyl diglycol carbonate, urethane-based resin, methacrylic resin, diallyl carbonate, polymethyl methacrylate, polycarbonate resin, thiourethane-based resin, episulfide-based resin, urethane methacrylate, epoxy methacrylate, and diallyl phthalate-based resin.

[0054] The thickness of the anti-fog coating layer is, for example, 1 μm or more and 50 μm or less, and preferably 3 μm or more and 20 μm or less.

[0055] The pencil hardness of the anti-fog coating layer is, for example, 3H or more and 9H or less, and in another example, 4H or more and 6H or less.

[0056] The anti-fog coating layer is formed, for example, by applying the anti-fog material according to the embodiment onto the surface of an optical substrate, drying the resulting coating film, and then heating the dried coating film. The drying temperature is, for example, 80°C or higher and 120°C or lower. The heating temperature is, for example, 80°C or higher and 200°C or lower, and the heating time is, for example, 1 hour or higher and 24 hours or lower. The drying time may not be included, and only the heating time may be included.

[0057] [Optical articles] The optical article according to the embodiment includes the cured body according to the embodiment. The optical article may include the laminate according to the embodiment.

[0058] Examples of optical articles include binder sheets, lenses, eyeglasses, window materials for houses and automobiles, liquid crystal displays, sun visors, watches, etc. Lenses include semi-finished lenses and finished lenses.

[0059] Fig. 2 is a cross-sectional view showing an example of glasses according to an embodiment. Glasses 100 shown in Fig. 2 include a lens 101 and a frame 102 that supports the lens 101. The lens 101 includes an optical article according to an embodiment. EXAMPLES

[0060] The present invention will be described in more detail with reference to some examples illustrated below. These examples are merely for the purpose of illustrating the present invention, and the spirit and scope of the present invention are not limited to these examples.

[0061] Example 1 1.1955g of HETESPU and 1.4040g of THF were stirred in an ice bath for 10 minutes, then 1.0533g of ion-exchanged water and 0.077g of methanol silica sol (30wt%, silica component 0.023g) were added, and the mixture was stirred in an ice bath for 10 minutes, then stirred at room temperature for 10 minutes, and further stirred at 70°C for 3 hours. After stirring, the solvent was removed by vacuum distillation and thermal vacuum drying to obtain 0.8267g of polymer as a viscous liquid. 0.0556g of the polymer was dissolved in 0.2232g of water to obtain a curable composition.

[0062] (Examples 2 to 13) Curable compositions were prepared in the same manner as in Example 1, except that the compositions were changed as shown in Table 1.

[0063] Example 14 0.8 g of BTESEAU, 7 mL of THF, and 30 μL of water were reacted at 70° C. to obtain a curable composition.

[0064] Example 15 0.8 g of BTESEAU, 7 mL of THF, 0.035 g of methanol silica sol (30 wt %, silica component 0.010 g), and 30 μL of water were reacted at 70° C. to obtain a curable composition.

[0065] <Evaluation test> 1. Manufacturing of anti-fog coated lenses The curable composition obtained in the examples was applied to a lens substrate and dried to obtain a dry film having a thickness of about 20 μm. A plastic lens or glass was used as the lens substrate. The drying conditions were room temperature. The dry film was heated to obtain a test lens having an anti-fog coating formed thereon. The heating conditions were 120 to 140° C. and 30 to 90 minutes.

[0066] In Comparative Example 1, a lens substrate without an anti-fog coating was used.

[0067] 2.Anti-fogging evaluation The anti-fogging properties of the test lenses obtained above were evaluated. Specifically, the test lenses were placed 2 cm above 50°C warm water, and the time until the lenses started to fog up was measured. The results are shown in Table 1. The fog time of Example 14 was 2.5 seconds, and the fog time of Example 15 was 2.5 seconds.

[0068] 3.Hardness The hardness of the test lenses obtained above was evaluated. Specifically, a pencil hardness test was carried out. The results are shown in Table 1. The hardness of Example 14 was 6H, and the hardness of Example 15 was 6H.

[0069] [Table 1]

[0070] Preferred embodiments of the present invention are described below.

[0071] [1] An anti-fogging material comprising an alkoxysilane having a urea bond.

[0072] [2] The anti-fogging material according to [1], wherein the alkoxysilane has a trialkoxysilane group represented by the following formula (I):

[0073] [ka]

[0074] In the formula (I), R 1 and R 2 each independently represents a linear or branched alkylene group having 1 to 10 carbon atoms, R 3 is a linear alkyl group having 1 to 5 carbon atoms, a is 0 or 1.

[0075] [3] The anti-fogging material according to [2], wherein the alkoxysilane includes a trialkoxysilane represented by the following formula (II):

[0076] [ka]

[0077] In the formula (II), R 1 , R 2 , R 3 and a are as defined above in formula (I), R 4 and R 5 each independently represents a linear or branched alkylene group having 1 to 10 carbon atoms, R 6 is -Si(OR 3 )3 or a hydroxy group, b is 0 or 1.

[0078] [4] The anti-fogging material according to [2], wherein the alkoxysilane includes a trialkoxysilane represented by the following formula (III):

[0079] [ka]

[0080] In the formula (III), X is a trialkoxysilane group represented by formula (I) above, and a plurality of X's may be the same or different groups; Y is nitrogen, a linear or branched alkylene group having from 1 to 10 carbon atoms, a cycloalkylene group having from 4 to 10 carbon atoms, or an arylene group having from 4 to 8 carbon atoms; R 7 is a linear or branched alkylene group having 1 to 10 carbon atoms; R 7 If there are multiple R 7 may be the same group or different groups, c is 0 or 1; d is 3 when Y is nitrogen and 2 when Y is a group other than nitrogen.

[0081] [5] The anti-fogging material according to any one of [1] to [4], wherein the content of the alkoxysilane is 10% by mass or more and 99% by mass or less.

[0082] [6] The anti-fogging material according to any one of [1] to [5], further comprising silica particles.

[0083] [7] The anti-fogging material according to any one of [1] to [6], further comprising an organic solvent having 1 to 5 carbon atoms, water, or a mixed solvent thereof.

[0084] [8] A cured product of the anti-fogging material described in any one of [1] to [7].

[0085] [9] An optical substrate; an anti-fog coating layer located on a surface of the optical substrate, the anti-fog coating layer comprising the cured product according to [8]; A laminate comprising:

[0086]

[10] An optical article comprising the cured product described in [8].

[0087]

[11] A lens comprising the optical article according to

[10] .

[0088]

[12] Eyeglasses comprising the lens described in

[11] .

Claims

1. An anti-fog material comprising an alkoxysilane having a urea bond.

2. 2. The anti-fogging material of claim 1, wherein the alkoxysilane has a trialkoxysilane group represented by the following formula (I): 【Chemistry 1】 In the formula (I), R 1 and R 2 each independently represents a linear or branched alkylene group having 1 to 10 carbon atoms, R 3 is a linear alkyl group having 1 to 5 carbon atoms, a is 0 or 1.

3. The anti-fogging material of claim 2, wherein the alkoxysilane comprises a trialkoxysilane represented by the following formula (II): 【Chemistry 2】 In the formula (II), R 1 , R 2 , R 3 and a are as defined above in formula (I); R 4 and R 5 each independently represents a linear or branched alkylene group having 1 to 10 carbon atoms, R 6 is -Si(OR 3 ) 3 or a hydroxy group, b is 0 or 1.

4. 3. The anti-fogging material of claim 2, wherein the alkoxysilane comprises a trialkoxysilane represented by the following formula (III): 【Chemistry 3】 In the formula (III), X is a trialkoxysilane group represented by formula (I), and a plurality of X's may be the same or different groups; Y is nitrogen, a linear or branched alkylene group having from 1 to 10 carbon atoms, a cycloalkylene group having from 4 to 10 carbon atoms, or an arylene group having from 4 to 8 carbon atoms; R 7 is a linear or branched alkylene group having 1 to 10 carbon atoms; R 7 When there are multiple R 7 may be the same group or different groups, c is 0 or 1; d is 3 when Y is nitrogen and 2 when Y is a group other than nitrogen.

5. The anti-fogging material according to claim 1 , wherein the content of the alkoxysilane is 10% by mass or more and 99% by mass or less.

6. 10. The anti-fog material of claim 1, further comprising silica particles.

7. The anti-fogging material according to claim 1 , further comprising an organic solvent having 1 to 5 carbon atoms, water, or a mixture thereof.

8. A cured product of the anti-fogging material according to claim 1.

9. An optical substrate; An anti-fog coating layer located on a surface of the optical substrate, the anti-fog coating layer comprising the cured product according to claim 8; A laminate comprising:

10. An optical article comprising the cured product according to claim 8.

11. A lens comprising the optical article of claim 10.

12. A pair of spectacles comprising a lens according to claim 11.

Citation Information

Patent Citations

  • Asymmetrically substituted polyorganosiloxane derivatives

    JP2018528289A

  • Curable composition

    JP2022071754A

  • Polymer material, heat-sealing material, Anti-fogging film and manufacturing method of polymer material

    JP2022152981A